Disclosure Status and Associated Factors Among Children on Antiretroviral Therapy in Ethiopia - Tucho WA (Pediatric Health, Medicine and Therapeutics, 2021)
Walelign Atomsa Tucho,1 Aderajew Nigusse Tekelehaimanot,2 Mahilet Berhanu Habte2 1Department of Disease Prevention and Control, Bench Sheko Zone Health Office, Mizan-Aman, Southwest Ethiopia; 2Department of Population and Family Health, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Mahilet Berhanu Habte Tel +251-912246413Email mahitesfa.mt@gmail.comBackground: The World Health Organization recommends that children should be informed of their HIV status at age 6– 12 years. However, disclosure of HIV status among children is very low in resource-limited areas, particularly in Ethiopia. So, the aim of this study was to determine the prevalence of disclosure and associated factors among a cohort of HIV-infected children in southwest Ethiopia.Methods: A facility-based cross-sectional study design was employed among caregivers of HIV-positive children aged 6– 15 in Bench sheko and West Omo zone Southwest Ethiopia, from March 1 to April 20, 2020. Study participants were included using a consecutive sampling technique. Data were collected using a pretested interviewer administered questionnaire and checklist. A multivariable logistic regressions model was used to identify independent predictors of disclosure. The significance of association was declared by AOR at 95% confidence and a p-value < 0.05.Results: A total of 327 participants were involved in the study yielding a 95% response rate. The prevalence of HIV-positive status disclosure was 45.6% (95% CI=41.01– 51.02). Caregiver secondary education and above (AOR=3.16, 95% CI=1.07– 9.34), caregiver discussed about disclosure with health professionals (AOR= 9.56, 95% CI=4.88– 18.74), child age 10– 15 year old (AOR=3.64, 95% CI=1.64– 8.08), duration on ART > 5 years (AOR=5.08, 95% CI=1.57– 16.37), treatment follow-up at hospital (AOR=2.23, 95% CI=1.27– 5.01) and having treatment support for Children (AOR=3.84, 95% CI=1.88– 7.85) were independent predictors of HIV-positive status disclosure.Conclusion: Disclosure of HIV status to children is low. Caregivers educational status, caregivers discussion with health professional, older child, duration on ART of more than 5 year, getting treatment service from hospital, and having a treatment support group are factors that enable disclosure. Therefore, concerted efforts based on the findings of this study will be required to improve the disclosure status among HIV-positive children.Keywords: disclosure, antiretroviral therapy, child